Heidegger's notion of truth as Alethia: a critical exposition - Itohowo Ignatius; Iniobong Umotong; Otto Dennis (Center for Humanities and Innovation Studies, 2022)
This paper is a critical exposition of Heidegger's concept of truth. The concept of truth has been an age-long discourse amongst scholars. This is because the notion cannot be extrapolated from man's being as a knowledge-seeking being. However, after many years of articulation and scholarship, questions like 'what constitutes truth?' or 'what is the nature of truth?' are yet to receive satisfactory answers. Every definition of truth tends to give rise to other perplexing philosophical problems. The three outstanding theories of truth (correspondence, coherence, and pragmatic theories) seem inefficient in answering the questions above. Heidegger then admonishes that we go back to the ancient Greek understanding of the notion, which meant 'unconcealment.' Upon this return, this research employs critical and analytic methods to expose the notion of truth as Aletheia, from Heidegger's perspective and its objections. Heidegger's truth is tied to the being of Dasein. He believes that truth only exists because Dasein exists to show it. This research asserts that when truth is regarded as Aletheia (disclosure), there are at least three repercussions of this character of truth. Truth is not limited to propositions; rather, it is discovered via many forms of Being-in-the-World. Second, truth is not only a matter of language and thought, but also the revelation of worldly creatures. Lastly, the truth, as Aletheia is constantly simultaneously exposing and hiding current events; that is, the truth is always in the process of becoming, as it is always in the process of being.